Chemical Bath Deposition of Co‐Doped TiO2 Electron Transport Layer for Hysteresis‐Suppressed High‐Efficiency Planar Perovskite Solar Cells. Issue 9 (11th July 2019) - Ren, Xiaodong; Xie, Lin; Kim, Won Bin; Lee, Dong Geon; Jung, Hyun Suk; Liu, Shengzhong (Frank)
Abstract : Planar hybrid perovskite solar cells (PSCs) attract great attention due to their obvious advantages of low‐temperature processing with a high power conversion efficiency (PCE) up to 23.32%. Here, Co‐doped TiO2 (Co‐TiO2 ) deposited by a straightforward low‐temperature chemical bath deposition (CBD) method is explored. Using Co‐TiO2 as an electron transport layer (ETL) for the planar PSCs, the effects of doping on TiO2 morphology, electronic properties, and solar cell performance are investigated. The PCE increases to 19.10% when the Co doping concentration is optimized at 5 mol%, an increase of 17.40% compared with that using the pristine TiO2 . Meanwhile, the notorious J – V hysteresis is suppressed to a greater extent. Considering that the low‐temperature CBD is comparable with continuous roll‐to‐roll processing, it makes the process and the Co‐TiO2 ETL potential candidates for low‐cost commercialization. Abstract : For developing low‐cost and high‐efficiency planar perovskite solar cells (PSCs), a straightforward low‐temperature chemical bath deposition process is developed to prepare a Co‐doped TiO2 (Co‐TiO2 ) electron transport layer (ETL); the optoelectrical properties of the TiO2 ETL are significantly improved by Co‐doping. Finally, the efficiency of the PSCs is increased from 17.40% for TiO2 to 19.10% for the Co‐TiO2 ETL.